EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DI DESA HAUWAI KECAMATAN HALONG KABUPATEN BALANGAN - Norsanti Norsanti; Wiwin Safitri (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2019)
The Hope Family Program (PKH) is one of the programs launched by the central government to reduce poverty in Indonesia. This program is implemented by providing non-cash assistance to poor households in the form of education and health assistance. In the authors' initial observations, it was found that there was an increase in the number of PKH participants in Balangan Regency, namely in 2017 only 2,219 households and in 2018 there were 3,863 households. The increase in the number of PKH program participants raises the question whether the program that has been running so far has been effective in reducing the existing poverty problems. The results showed that the Family Hope Program (PKH) in the village of Hauwai was effective enough to help people who were very poor and vulnerable especially to access education and health. The factors that influence the effectiveness of the Family Hope Program (PKH) are KPM's willingness to fulfill its obligations as well as facilities and infrastructure for Very Poor Family (KPM) coordinators and assistants.